RESULTS OF IMMEDIATE FACIAL NERVE RECONSTRUCTION IN PATIENTS UNDERGOING PAROTID TUMOUR RESECTION - Rashid, Haroon Ur; Rehman, Ishtiaq Ur; Rashid, Mamoon; Yousaf, Shumaila; Khan, Nasir; akhtar, Aqsa (Journal of Ayub Medical College Abbottabad, 2019)
Background: Facial nerve is usually sacrificed in total parotidectomy. The objective of this study is to present results of immediate reconstruction of facial nerve in total parotidectomy cases where facial nerve is sacrificed. Methods: This is a prospective study done in patients who had total parotidectomy including facial nerve and immediate reconstruction was done with inter-positional nerve grafts (sural n=12 and greater auricular n=10) from December 2017 till February 2018 by single surgeon (MR). Wounds were closed primarily (n=15), local flap (n=2) and free flap (n=5). Clinical evaluation was done at four months minimum follow up (those operated in January to February 2018) and eight months maximum follow up (those operated in December 2017), for facial nerve functional recovery using House and Brackmann grading system by single author (MR). Results: Total of 22 (male n=7, female n=15) patients included in study from December 2017 till February 2018. Sural nerve grafts were used in 54% (n=12) and greater auricular nerve grafts in 45% (n=10) patients for reconstruction of facial nerve. On clinical evaluation using House and Brackmann grading system, showed grade V (n=4), grade IV (n=7), grade III (n=8) and grade II (n=3) repairs. Conclusion: Although primary end to end facial nerve repair is ideal but in situation where a significant segment of nerve is lost or where the repair is under tension, inter-positional nerve grafting is a simple and reliable reconstructive technique with good outcomes. Keywords: Facial nerve immediate reconstruction; total parotidectomy; sural nerve grafts; Facial nerve palsy; House and Brackmann grading; facial reanimation